Intraseasonal Variability of the East Asia-Pacific Teleconnection and Its Impacts on Multiple Tropical Cyclone Genesis Over the Western North Pacific - Lin, Xin; Wang, Lan; Gao, Jianyun; Chen, Xiaoxiao; Zhang, Wei (Frontiers in Earth Science, 2021)
A daily East Asia-Pacific teleconnection (EAP) index was constructed to investigate the impact of the intraseasonal variability (ISV) of this index on the genesis of multiple tropical cyclones (MTC) in boreal summer over the western North Pacific (WNP). The result indicates that the EAP index has dominant intraseasonal periods of 10-20 days, 20-40 days and 50-70 days, respectively. The ISV of the EAP during 1979-2019 can be classified into three types, a single-period-domination type (37%), a multiple period coexistence type (24%) and a transition type (39%). It is found that during El Niño (La Niña) summers, the ISV of the EAP is dominated by a higher-frequency (lower-frequency) oscillation with a period of around 20-30 (50-70) days. The distinctive ISV characteristics during the different ENSO years were accompanied with different dynamic and thermodynamic background conditions over the WNP and the South China Sea, which modulated the frequency and location of MTC genesis. By examining the relative contributions of individual environmental variables of the Genesis Potential Index (GPI), we found that the low-level absolute vorticity and mid-level relative humidity are two important environmental factors modulating MTC genesis. However, the relative role of these variables tends to change with the EAP ISV phase. The environmental condition over the SCS appears less influenced by ENSO. A more southern location of MTC genesis during El Niño is attributed to the change of the environmental humidity.